FEATURES OF THE ORGANIZATION OF DISTANCE EDUCATION IN THE NATIONAL AVIATION UNIVERSITY - But, Volodymyr Anatoliiovych; Hnatiuk, Viktor Oleksandrovych (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2021)
The modern market for educational services adapts to the demands of people and circumstances. The COVID-19 pandemic and quarantine have made adjustments to the education of bachelors and masters in almost all universities around the world. The transition to online education using modern Internet technologies has led to certain problems in the higher education system. The National Aviation University switched to distance learning based on the Google Workspace platform a year ago. The aim of the work is to study the peculiarities of the organization of the educational process at the National Aviation University during the pandemic COVID-19. Also, the paper analyzes the solutions used in Google Workspace to ensure cybersecurity.